Antimicrobial overuse and misuse in the community in Greece and link to antimicrobial resistance using methicillin-resistant S. aureus as an example - Stamatis Karakonstantis; Dimitra Kalemaki (Elsevier, 2019)
Both antimicrobial consumption and antimicrobial resistance are very high in Greece, ranking among the highest of Europe. The link between antimicrobial consumption and resistance is well-known. Here, we discuss the reasons of antimicrobial overuse in Greece in the community (such as self-medication, dispersion of antibiotics by pharmacies without prescription, over-prescription by physicians, patient expectations and liability pressure) and we explore the misuse of antibiotics for common community infections. Furthermore, we discuss how such overuse/misuse can drive antimicrobial resistance, using methicillin-resistance in Staphylococcus aureus as an example. S. aureus is one of the pathogens with high rates of resistance in Greece. Comparing the rate of antimicrobial susceptibility to non-beta lactams between methicillin-resistant and methicillin-sensitive S. aureus we highlight the antibiotics that have the potential to drive methicillin-resistance through co-selection. Based on the above we identify targets for intervention in order to reduce antimicrobial overuse/misuse in the community in Greece. Keywords: Staphylococcus aureus, MRSA, Resistance, Antibiotic overuse, Greece, Epidemiology